The Importance of the Governor Regulation in Supporting the Geographical Indication of Batik Production in West Java - Komarudin Kudiya; Saftiyaningsih S. Ken Atik (Fakultas Hukum Universitas Muhammadiyah Yogyakarta, 2020)
West Java has traditional batik crafts developed in 27 districts/cities. The diversity in both style and variation af this traditional batik is a source of strength that is not found in other provinces. The spread of imitation batik (batik motif) put a serious threat for traditional batik craftsmen. The purpose of this research is to discuss the importance of regulating the use of traditional batik to increase the economic value and to support the geographical indication in West Java. This empirical legal research used both secondary and primary data. It is found that the regulation on the use of traditional batik as governed under the Governor Regulation is intended to increase the economic value and to support the geographical indication of West Java Province. This regulation is a strategic step in efforts to preserve, develop, and protect the existence of West Java traditional batik.